Place attachment and perception of climate change as a threat in rural and urban areas. - Thora Tenbrink; Simon Willcock (PLoS ONE, 2023)
Climate change is a global threat to ecosystems and the people that depend on them. However, the perceived threat of climate change may vary spatially. Previous research suggests that inhabitants in rural areas show higher levels of place attachment (associating meaning with a specific place) than urbanites, possibly because rural people depend more directly on their local environment. This can shape perceptions and behaviours, such as enhanced willingness to engage in landscape preservation. Here we ask if it also makes rural people perceive climate change as a greater threat, using a representative sample of 1,071 survey respondents from across the United Kingdom (UK) to provide first-order insights. We found that, whilst indicators of place attachment were indeed more frequent in rural areas, the perceived threat of climate change in the most rural locations was lower. We discuss possible explanations for this pattern (including lower levels of awareness of the anthropogenic causes of climate change, lessened first-hand experiences of climate change impacts due to higher levels of regulating ecosystem services, and higher levels of resilience in rural areas related to a closer relationship with nature), and call for further research to investigate this.